Decision support systems - collaborative models and approaches in real environments Euro Working Group Workshops, EWG-DSS 2011, London, UK, June 23-24, 2011, and Paris, France, November 30 - December 1, 2011, revised selected and extended papers - Hernandez, Jorge E. (Lecture Notes in Business Information Processing,, 2012)
This book contains extended and revised versions of a set of selected papers from two workshops organized by the Euro Working Group on Decision Support Systems (EWG-DSS), which were held in London and Paris, in June and November 2011, respectively. The workshop themes were "Decision Support Systems" and "Collaborative Decision Making." The 11 papers were selected from 52 submissions and are representative of the current research in these fields. They address challenges such as conceptual models, software specification and simulation, collaborative requirements specification, as well as multi-objective and multi-criteria decision making.